Integral Framework as a Systemic Foundation for Coaching - Matti Kamppinen; JP Jakonen (My University, 2022)
Coaching as a combination of cognitive and behavioral techniques can be founded
upon different knowledge bases, or frameworks. Like positive psychology or
consulting psychology, coaching utilizes theories from developmental
psychologies and other knowledge bases concerning human transformation. We
argue that systemic coaching is best facilitated by the integral framework that
acknowledges the diversity and multi-faceted nature of human existence.
Following Ken Wilber and Robert Kegan, we reconstruct and discuss integral
coaching (as developed by Joanne Hunt and Laura Divine) as a systemic coaching
approach that is based on integral framework. We conclude that the integral
framework is needed not only for truly systemic coaching, but also for the
construction of wisdom cultures that acknowledge the big picture, or systemic
relationships beyond one’s immediate surroundings
Keywords: integral framework, integral coaching, four quadrants model, AQAL
model, knowledge base of coaching, developmental psychology, adult thinking,
positive psychology, consulting psychology, wisdom culture